Genotypic variations in root traits of wheat varieties at phytomer level (Journal of the Bangladesh Agricultural University, 2014)
The aims of this study were to investigate genotypic variations in root traits at phytomer level of wheat varieties and for recommending a few root traits as selection parameters in future breeding programs. Two separate experiments were conducted to measure their root traits for hydroponically grown wheat plants. In Experiment 1, main axis length, root hair density and diameter differed from phytomer to phytomer at 60 days after sowing for two varieties, Shotabdi and Sonalika. Density of first order laterals at their axis of origin, dry weights of roots and shoots and root:shoot ratio varied significantly among 8 varieties. In Experiment 2, number of root bearing phytomer, total number of adventitious roots, main axis length at root bearing phytomer 1 and 2 (youngest roots were the reference point and numbered as phytomer 1), length of first order laterals at phytomer 3, root hair density and dry weights of roots and shoots were significantly different among varieties. PC1 (principal component 1) resulted in significant variation among varieties for number of live leaves, new roots appeared, number of root bearing phytomer, total number of adventitious roots, root dry weight and shoot dry weight. PC2 yielded significant difference among varieties for live leaves, main axes length at phytomer 1 & 2, number of new roots, root hair density and diameter. Selection of varieties based on main axes length at the youngest phytomer & root hair density per unit surface area along with dry weights of roots and shoots could be recommended for future breeding program as these four parameters consistently resulted in significant variation among varieties. DOI: http://dx.doi.org/10.3329/jbau.v12i1.21238 J. Bangladesh Agril. Univ. 12(1): 45-54, June 2014